Comparative analysis of margin status in breast conservation surgery and its correlation with subsequent re-excision findings - Krishnamurthy, K.; Febres-Aldana, C.A.; Alghamdi, S.; Mesko, T.; Paramo, J.; Poppiti, R. J. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Purpose. Breast-conservation surgery (BCS) has become a standard treatment option for invasive breast carcinoma (IBC) and ductal carcinoma in situ (DCIS). The strongest predictor of local recurrence remains the surgical margin status. We evaluated the margin positivity by quantifying the tumor on positive margins and analyzing the histologic factors including type and extent in determining the likelihood of residual disease upon re-excision. Method. Retrospective analysis of 210 BCS performed at Mount Sinai Medical Center from the period of January 2011 - December 2017 revealed that 58 had IBC, DCIS, or both, with positive margins that were followed by re-excision. Result. The margins had IBC in 18 (31%), DCIS in 32 (55.2%) and both in 8 (13%) cases. Thirty-eight cases (65.5%) were free of carcinoma on re-excision. Of 40 cases with margins positive for DCIS, 16 (40%) had residual DCIS. Of 26 cases with IBC at the margins, and 5 had residual disease (19%). This difference was statistically significant (p = 0.002). Of 21 cases with extensive DCIS, 12 had residual disease (p = 0.02) as compared to only 4 out of 19 without extensive DCIS. None of the cases with clinging/micro-papillary DCIS had residual disease, while 51% of the other types (solid, cribriform, come-do) had residual disease (p = 0.02). The area of DCIS as measured on the involved margin correlated with the amount of residual disease on re-excision (p = 0.03). Conclusion. Margins positive for DCIS are more likely to have residual disease on re-excision in comparison to margins positive for only IBC. The type and extent of DCIS appears to influence the likelihood of residual disease.